Status Epileptikus: Darurat Medis dan Neurologis - Ath Thahirah Annisa Fajra; Herlina Sari (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Emergency conditions refer to situations that require immediate intervention because they have the potential to threaten life, impair organ function, or cause disability if not managed promptly and appropriately. Status epilepticus is a neurological emergency defined by seizures lasting five minutes or longer, or by repeated seizures without regaining consciousness between episodes. Status epilepticus can develop in individuals both with and without a previous diagnosis of epilepsy and may result from a wide range of causes, such as metabolic abnormalities, infections of the central nervous system, stroke, head injury, sudden discontinuation of antiepileptic medications, and alcohol intoxication or withdrawal. Clinically, this condition is classified into convulsive and non-convulsive status epilepticus. The diagnosis is primarily clinical and must be established rapidly, while electroencephalography plays an important role, particularly in cases of non-convulsive status epilepticus. Management emphasizes initial stabilization of the airway, breathing, and circulation, after which benzodiazepines are given as first-line treatment, including intramuscular midazolam, intravenous lorazepam, or intravenous diazepam. Status epilepticus represents the most severe form of seizure activity, characterized by continuous, unremitting seizures accompanied by strong muscle contractions, respiratory compromise, and widespread abnormal electrical activity in the brain. If not treated promptly, the risk of permanent brain tissue damage increases and the condition may ultimately lead to death.